In silico test of cytotoxic activity and toxicity of guava leaf compounds (Psidium guajava) as a drug for diabetes mellitus - Aisha Azaria Nisa’ul Khoiro; Moh. Mirza Nuryady (Universitas Muhammadiyah Malang, 2025)
Background: Diabetes mellitus is a metabolic disorder caused by a lack of the hormone insulin. Diabetes mellitus is characterized by elevated blood glucose levels due to the inactivity of the GLP-1 protein, which leads to decreased insulin function. Guava leaves (Psidium guajava) are suspected to have antidiabetic effects, but the active compound responsible for lowering blood glucose levels is unknown. Objectives: The aim of this study was to determine the physicochemical properties and toxicity as well as the mechanism of active compounds of guava leaves using In Silico studies. Methods: The method in this research is a computer-based experiment in the form of Molecular docking, by comparing the active compounds in guava leaves with the target protein GLP-1. Results: The results of the In Silico test show that the Caryophyllene and Cadala compounds have binding affinities of -7.8 and -6.9 and the toxicity class for caryophyllene is class 6, which indicates that the compound is not toxic, while for cadala the toxicity class is included in class 5, which indicates that it may be harmful if swallowed. Conclusion: The compounds Cadala and Caryophyllene demonstrated that further testing is warranted to determine the proportions required to maintain their safety. Meanwhile, benzene was not considered a drug candidate because its carcinogenicity was shown to be active in toxicity tests, suggesting it cannot be used as a drug candidate for diabetes mellitus.